Care Bundle Application Decreases The Frequency and Severity of Intraventricular Hemorrhage in Preterm Neonates: Single Center Study - Sarah S. El Tatawy; Amira M. Gad; Tamer S. Eissa; Salma Z. El Houchi; Amira M. Sabry (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Intraventricular hemorrhage (IVH) is a severe complication in preterm babies admitted to Neonatal Intensive Care Units (NICU). Advanced stages of IVH predispose to neurological deficits such as cerebral palsy and hydrocephalus. There are numerous strategies and policies implemented in NICUs around the world to decrease the incidence of IVH in preterm babies and prevent its ensuing neurodevelopmental complications. Aim of the Work: To study the effect of implementing a bundle of care on incidence and severity of IVH among preterm neonates. Materials and Methods: Retrospective analysis of patient records for incidence and severity of IVH between May and August 2018 was done. This was followed by an educational interim period where NICU staff received training of pre-natal, natal, and postnatal care bundle guidelines to reduce IVH. The guidelines were then implemented on all preterm babies (28-34 weeks gestational age (GA)) born and admitted to Kasr Al Ainy Teaching Hospital NICU, Cairo University between October 2018 and January 2019 (n=58). Cranial ultrasonography was performed at week 1 and week 2-3 of life. Frequency and severity of IVH were compared among studied groups. Risk factors for IVH were analyzed and recorded. Results: The frequency of IVH was significantly lower in the post-bundle group (44-46% pre-bundle, and 27% post-bundle) especially evidenced by the ultrasonography in week two of life. Severity of IVH also improved post bundle since there were no grade III IVH patients in that group. Exposure to hypocapnia, blood pressure fluctuations, IV fluid boluses and administration of sodium bicarbonate were significantly correlated with development of IVH in preterm babies (p = 0.001). Conclusion: Implementation of an IVH care bundle that includes perinatal measures can positively affect the neurological outcome by decreasing incidence and severity of IVH in preterm babies.